Transformasi Komunikasi Digital: Landasan Teoretis dan Evolusi Teknologi di Era Jaringan Global - Fathimah, Laila; Nasution, Wahyuddin Nur; Padli Nasution, Muhammad Irwan (Universitas Pahlawan Tuanku Tambusai, 2025)
The development of communication technology has undergone a revolutionary leap, transforming human interaction and shapingsocial structures in the digital era. This article aims to examinethe basic concepts, historical evolution, and main theories in thestudy of communication technology. Using a qualitative approachbased on literature study, the discussion includes digital integration, media convergence, and issues such as socialpresence and media dependency. This article highlights thatcommunication technology is not merely a technical tool but alsoshapes new social realities. The analysis indicates that theoreticalunderstanding of communication technology development isessential for formulating policies, educational strategies, andsustainable digital literacy programs.